Exploring the question‐behaviour effect: Randomized controlled trial of motivational and question‐behaviour interventions. (23rd April 2012) - Ayres, Karen; Conner, Mark; Prestwich, Andrew; Hurling, Robert; Cobain, Mark; Lawton, Rebecca; O'Connor, Daryl B.
<x xml:space="preserve">Abstract</x> Purpose. Measuring intentions and other cognitions to perform a behaviour can promote performance of that behaviour (the question‐behaviour effect, QBE). It has been suggested that this effect may be amplified for individuals motivated to perform the behaviour. The present research tested the efficacy of combining a motivational intervention (providing personal risk information) with measuring intentions and other cognitions in a fully crossed 2 × 2 design with an objective measure of behaviour in an at‐risk population using a randomized controlled trial (RCT). Methods. Participants with elevated serum cholesterol levels were randomized to one of four conditions: a combined group receiving both a motivational intervention (personalized cardiovascular disease risk information) and a QBE manipulation (completing a questionnaire about diet), one group receiving a motivational intervention, one group receiving a QBE intervention, or one group receiving neither. All participants subsequently had the opportunity to obtain a personalized health plan linked to reducing personal risk for coronary heart disease. Results. Neither the motivational nor the QBE manipulations alone significantly increased rates of obtaining the health plan. However, the interaction between conditions was significant. Decomposition of the interaction indicated that the combined condition (motivational plus QBE manipulation) produced significantly higher rates of obtaining the health plan (96.2%) compared to the other three groups combined (80.3%). Conclusions. The findings provide insights into the mechanism underlying the QBE and suggest the importance of motivation to perform the behaviour in observing the effect. Statement of Contribution What is already known on this subject? Research has indicated that merely asking questions about a behaviour may be sufficient to produce changes in that or related behaviours (referred to as the question‐behaviour effect; QBE). Previous studies have suggested that the QBE may be moderated by the individual's motivation to change the behaviour, i.e., the QBE will only produce increases in the behaviour among those with strong motivation to perform the behaviour. However, no study has directly tested this prediction by manipulating motivation and examining impacts on the QBE. What does this study add? The present study tested the individual and combined effects of a motivational and a QBE intervention in a fully crossed design using a randomized controlled trial (RCT) and showed that: a combined intervention significantly increased behaviour. effect partially mediated by cognitions.